“Are We Allowed to Refer Patients?”: U.S. Physician Experiences Facilitating Abortion Care in a Restricted State - Corinne M. Hale; Laura Jacques; Eliza Bennett; Jenny A. Higgins; Abigail S. Cutler (Perspectives on Sexual and Reproductive Health, 2026)
ABSTRACT Objective Few studies have examined how abortion referrals occur in settings that criminalize or restrict most abortion care. We aimed to document how Wisconsin obstetrician‐gynecologists (OB‐GYNs) facilitated abortion care for patients while practicing under the threat of a criminal ban following the elimination of federal abortion rights protection. Methods We recruited 21 OB‐GYNs from diverse practice settings in virtual interviews between September and December of 2023. Interviews explored experiences providing pregnancy care and facilitating abortion under institutional policies both before and following threatened enforcement of a state criminal abortion law. Investigators coded and analyzed data using a combined inductive‐deductive approach. Results We identified three themes regarding how Wisconsin OB‐GYNs facilitated abortion under a statewide ban. First, physicians faced legal fog and lack of institutional guidance, leading to highly varied referral practices. Second, the lack of robust referral pathways had negative impacts for both physicians and patients. Third, many physicians were left to patch together their own abortion referral systems, leading to unique physician burdens. Conclusions While abortion services were unavailable, Wisconsin's systems to facilitate abortion for patients were inadequate or absent, leaving OB‐GYNs with informal and unconventional means to help patients access care within—and across—state lines. In settings where abortion is banned or severely restricted, referrals may rely heavily on healthcare institutional‐level referral pathways and patient navigation systems. In such settings, institutions should help facilitate timely abortion access for patients and ease burdens on physicians by establishing and supporting robust referral systems and patient‐centered navigation services.